Climate Smart Agriculture investment plans - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The CSA Investment Plans have been developed and passed: (1) the World Bank Quality Enhancement Review (QER); (2) World Bank Decision Meeting; (3) validation workshops by both countries of Mali and Cote d'Ivoire. The World Bank is now actively looking to scale the approach out to four additional countries.